PENGEMBANGAN E-LKPD MENGGUNAKAN LIVEWORKSHEET PADA SUBTEMA BENDA TUNGGAL DAN CAMPURAN - Suci Maghrisya Putri; Yuli Mulyawati; Ratih Purnamasari (STKIP Subang, 2024)
Suci Maghrisya Putri. 037120067. This research aims to develop E-LKPD using Liveworksheets for class V students at SDN Cibuluh 4 Bogor City and to determine the feasibility of E-LKPD using Liveworksheets for the learning process carried out at school. The method in this research uses the Research and Development (R&D) method using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation). The research subjects were class V students at SDN Cibuluh 4, Bogor City, consisting of 29 students in the even semester of the 2023/2024 academic year. The research results show that developing E-LKPD using live worksheets is feasible. This can be seen from the results of validation tests carried out by media experts who obtained 80% with appropriate criteria, validation of language experts obtained 100% with very appropriate criteria, validation of lecturer material experts obtained 96% with very appropriate criteria, validation of teacher material experts obtained 92% with very feasible criteria. The results of the student response questionnaire obtained 90% with very decent criteria, and the average N-Gain score for learning outcomes was 0.72 with high criteria. So, these results show that E-LKPD using Liveworksheets is very suitable for use in the learning process and is very effective in improving student learning outcomes.